SISTEM PACKET SWITCHING PADA FAKSIMILI - Agus Sugiharto (JURNAL MITRA MANAJEMEN, 2019)
Switching is a connection process, in communicating this switching is responsible for connecting the sender and receiver (Tx and Rx). In data communications there are three known systems of Switching, Circuit Switching, Massage Switching and Packet Switching. Sircuit Switching can also be used for voice communication, but Massage Switching and Switching Packages are not used in voice communication, because the two systems undergo a Store and Forword process. The combination of switching systems can also be carried out in communication networks such as the facsimile communication service network provided by PT. INDOSAT. Customers who are members of the Public Switching Telephone Network (PSTN) network use a Circuit Switching system but after joining the fax network in Indosat, the switching system used has changed to a Packet Switching system. Indosat Fasimili service customers who use the packet switching system will be able to deliver to multiple destinations with one access which will be able to reduce communication costs on the PSTN network and can make delivery schedules according to the customer's wishes. This added value is a communication advantage through Indosat fax services supported by the System Store and Forward (Packet Switching System)